New Voices of The Boudoir Repinings Poems: Research on Chinese Popular Songs Inheritance and Development of The Traditional Boudoir Repinings Poems - Wang, Yi (Tanjong Malim, 2023)
New Voices of The Boudoir Repinings Poems: Research on Chinese Popular Songs Inheritance and Development of The Traditional Boudoir Repinings Poems by Wang, Yi